Usefulness of HSC and HSG in the estimation of acquired uterine changes, size and shape in infertile patients - Milnerowicz-Nabzdyk, Ewa; Zimmer, Mariusz (Menopause Review/Przegląd Menopauzalny, 2004)
Summary Objectives: To compare the usefulness of two methods: hysteroscopy (HSC) and hysterosalpingography (HSG) in diagnostics of acquired uterine changes, size and shape. Design: The results of hysteroscopic and hysterosalpingographic examination of acquired uterine changes, size and shape were compared. Compatibility, sensitivity and specificity of both methods in each case of uterine changes were estimated. Materials and methods: The results of both HSC and HSG examinations performed in 222 infertile women day by day were analyzed. Detected acquired uterine changes included polyps, myomas, adhesions and focal hypertrophy. Results: The results of HSC and HSG were compared. Polyps in the uterine cavity were detected in 8 patients in HSC and in 2 – in HSG, the agreeable results were observed in 2 cases. The myomas in the uterine cavity were observed in 12 cases in HSC and 12 in HSG, the agreeable results concerned 8 cases. Intrauterine adhesions – in 4 cases in HSC, and in 2 cases in HSG, in 1 case the results were agreeable; focal hyperplasia in 16 patients in HSC, in 12 in HSG and agreeable results in 9 cases. Counting specificity and sensitivity – both methods have almost equal specificity range of 96-99%. HSC is absolutely a more sensitive method than HSG in the diagnostics of polyps, myomas, adhesions and focal hypertrophy. Both methods are supplementary to each other in the estimation of the size and shape of uterus. Conclusions: HSC is a more sensitive method than HSG in the diagnostics of acquired uterine changes and both methods are equally specific in the diagnostics of these changes. Both methods play a supplementary role in the estimation of size and shape of uterus.